Comparison of thiol subproteome of the vent mussel Bathymodiolus azoricus from different Mid-Atlantic Ridge vent sites - Company, Rui (2020)
Deep-sea hydrothermal mussels Bathymodiolus azoricus live in the mixing zone where hydrothermal fluid mixes with bottom seawater, creating large gradients in the environmental conditions and are one of the most studied hydrothermal species as a model of adaptation to extreme conditions. Thiol proteins, i.e. proteins containing a thiol or sulfhydryl group (SH) play major roles in intracellular stress defense against reactive oxygen species (ROS) and are especially susceptible to oxidation. However, they are not particularly abundant, representing a small percentage of proteins in the total proteome and therefore are difficult to study by proteomic approaches. Activated thiol sepharose (ATS) was used for the rapid and quantitative selection of proteins comprising thiol- or disulfide-containing subproteomes. This study aims to isolate thiol-containing proteins from the gills of B. azoricus collected in distinct hydrothermal vents and to study the thiol-containing subproteome as a function of site-specific susceptibility to ROS. Results show that ATS is a powerful tool to isolate the thiol-containing sub-proteome and differently-expressed protein spots showed significant differences among the three vent sites, supporting previous findings that specific environmental conditions are crucial for ROS formation and that B. azoricus have different susceptibilities to oxidative stress depending on the vent site they inhabit.